Effect Of Planting Geometry On Growth Of Rice Varieties - Mahato, Mohan; Adhikari, Bishnu Bilas (International Journal of Applied Sciences and Biotechnology, 2017)
A field experiment was conducted under humid subtropical agro-climatic condition of Nepal during rainy season of 2014. The experiment was laid out in to two factor Randomized Complete Block Design with three replications consisting three drought tolerant rice varieties (Sukhadhan-4, Sukhadhan-5 and Radha-4) and four planting geometry (15 cm × 10 cm, 15 cm × 15 cm, 20 cm × 15 cm and 20 cm × 20 cm). The results revealed that the highest plant height and maximum leaf area index was recorded in planting geometry 15 cm × 10 cm in all growth stages. Whereas, planting geometry 20 cm × 15 cm produced the maximum number of tiller m-2 in all growth stage. While planting geometry 20 cm × 15 cm and 20 cm × 20 cm produced statistically similar crop growth rate and dry matter accumulation in all stage of growth. Regarding the varieties, Sukhadhan- 4 showed highest plant height up to 75 DAT and plant height was statistically similar to Radha - 4 in 60 and 75 DAT. But maximum number of tiller m-2, leaf area index, crop growth rate and dry matter accumulation were recorded in Sukhadhan – 5 varieties. Int. J. Appl. Sci. Biotechnol. Vol 5(4): 423-429